Activity and safety of pegylated liposomal doxorubicin, 5-fluorouracil and folinic acid in inoperable hepatocellular carcinoma: A phase II study - Lorenzo, Giuseppe Di (World J Gastroenterol, 2007)
AIM: To improve the results of New therapeutic strategies in hepatocellular carcinoma (HCC). We have conducted a phase II study with pegylated liposomal doxorubicin (PLD), 5-fluorouracil (5FU) and folinic acid (FA). METHODS: Thirty-one patients with hystologically-confirmed, inoperable HCC, received combination chemotherapy with PLD 25 mg/mq on d 1, 5FU 1200 mg/mq in 48 h continuous infusion, and oral FA 30 mg on d 1 and 2 every 3 wk until disease progression or intolerable toxicity. RESULTS: The median age was 65 years (range 41-82) and 28 patients were hepatitis C virus seropositive (90%). The majority of patients were Child-Pugh Class B (55%). Two patients showed a partial response (PR), and 16 had stable disease (SD). With a median follow-up of 14 mo, the median time to progression of all evaluable patients was 4 mo (95% CI 1.7-7). Median overall survival was 9 mo (95% CI 3-24 mo). After 1 year, 9 of 18 PR/SD patients were alive. Chemotherapy was well tolerated. CONCLUSION: PLD/FU/FA combination seems capable of achieving durable stabilization of HCC. The manageable toxicity supports a role for combination with other anticancer agents.